California Painters : New Work - Hopkins, Henry T. (San Francisco : Chronicle Books San Francisco, 1989)
Albuquerque, Lita ; Alexander, Peter ; Almaraz, Carlos ; Bengston, Billy Al ; Bischoff, Elmer ; Brice, William ; Brown, Christopher ; Brown, Joan ; Burkhardt, Hans ; Colescott, Robert ; Corse, Mary ; Diebenkorn, Richard ; de Forest, Roy ; Foulkes, Llyn ; Francis, Sam ; Garabedian, Charles ; Garcia, Rupert ; Giegerich, Jill ; Goode, Joe ; Herman, Roger ; Hockney, David ; Hudson, Robert ; Jackson, Oliver ; Jackson, Richard ; Jess ; Kauffman, Craig ; Lundeberg, Helen ; Moses, Ed ; Mullican, Lee ; Oliveira, Nathan ; Onslow-Ford, Gordon ; Romero, Frank ; Ruscha, Edward ; Saunders, Raymond ; Smith, Alexis ; Tansey, Mark ; Teraoka, Masami ; Thiebaud, Wayne ; Treiman, Joyce ; Woelffer, Emerson ; Wonner, Paul
Biog. auteurs flaptekst
Engels
boek
Keywords: California; Verenigde Staten; U.S.A.